2021
DOI: 10.3390/pr9020266
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Hydropower Turbine Using Seawater from a Fish Farm

Abstract: Discharge water from fish farms is a clean, renewable, and abundant energy source that has been used to obtain renewable energy via small hydropower plants. Small hydropower plants may be installed at offshore fish farms where suitable water is obtained throughout the year. It is necessary to meet the challenges of developing small hydropower systems, including sustainability and turbine efficiency. The main objective of this study was to investigate the possibility of constructing a small hydropower plant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Moreover, the efficiency increased to 5.56% at 0.17 m 3 /min, and the average efficiency increased to 6.27%. It is understood that changing the shape of the impeller and casing is the best solution to improving a pump's performance [43]. Figure 18 shows the cross-sectional view of the original and newly designed impellers.…”
Section: Optimum Modelmentioning
confidence: 99%
“…Moreover, the efficiency increased to 5.56% at 0.17 m 3 /min, and the average efficiency increased to 6.27%. It is understood that changing the shape of the impeller and casing is the best solution to improving a pump's performance [43]. Figure 18 shows the cross-sectional view of the original and newly designed impellers.…”
Section: Optimum Modelmentioning
confidence: 99%
“…Moreover, the efficiency increased to 5.56% at 0.17 m 3 /min, and the average efficiency increased to 6.27%. It is understood that changing the shape of the impeller and casing is the best solution to improve the pump's performance [42]. Figure 18 shows the cross-sectional view of the original and newly designed impeller.…”
Section: Optimum Modelmentioning
confidence: 99%
“…In total, four crossflow turbines with 24 blades and the same height (0.3 m) were tested at a water flowrate ranging from 0.02 to 0.06 m 3 The diameters of the turbines were 0.4, 0.5, 0.6, and 0.7 m, and the overall efficiency is shown in Table 5. Testing all turbines in the same setting (vortex-driven generator system) revealed that the five-blade propeller turbine with a 0.4 m height and 0.7 m diameter [21] achieved the highest efficiency of 13.92% at the 0.02 m 3 /s water flowrate.…”
Section: The Comparisonmentioning
confidence: 99%
“…The results were used as parameters in order to maximize the benefit of these kinds of power plant [2]. There are also many studies and developments on hydroelectricity, innovations in the transportation business and power industries, such as research on the development of a hydropower turbine using seawater from a fish farm [3].…”
Section: Introductionmentioning
confidence: 99%